Promoter cloning and characterization of the human programmed cell death protein 4 (pdcd4) gene: evidence for ZBP-89 and Sp-binding motifs as essential Pdcd4 regulators - Leupold, Jörg; Mudduluru, Giridhar; Allgayer, Heike (Bioscience reports, 2012)
Pdcd4 (programmed cell death protein 4) is an important novel tumour suppressor inhibiting transformation, translation, invasion and intravasation, and its expression is down-regulated in several cancers. However, little is known about the transcriptional regulation and the promoter of this important tumour suppressor. So far the following is the first comprehensive study to describe the regulation of Pdcd4 transcription by ZBP-89 (zinc-finger-binding protein 89), besides characterizing the gene promoter. We identified the transcriptional start sites of the human pdcd4 promoter, a functional CCAAT-box, and the basal promoter region. Within this basal region, computer-based analysis revealed several potential binding sites for ZBPs, especially for Sp (specificity protein) family members and ZBP-89. We identified four Sp1/Sp3/Sp4-binding elements to be indispensable for basal promoter activity. However, overexpression of Sp1 and Sp3 was not sufficient to enhance Pdcd4 protein expression. Analysis in different solid cancer cell lines showed a significant correlation between pdcd4 and zbp-89 mRNA amounts. In contrast with Sp transcription factors, overexpression of ZBP-89 led to an enhanced expression of Pdcd4 mRNA and protein. Additionally, specific knockdown of ZBP-89 resulted in a decreased pdcd4 gene expression. Reporter gene analysis showed a significant up-regulation of basal promoter activity by co-transfection with ZBP-89, which could be abolished by mithramycin treatment. Predicted binding of ZBP-89 to the basal promoter was confirmed by EMSA (electrophoretic mobility-shift assay) data and supershift analysis for ZBP-89. Taken together, data for the first time implicate ZBP-89 as a regulator of Pdcd4 by binding to the basal promoter either alone or by interacting with Sp family members.